Antibacterial Activity of Graphdiyne and Graphdiyne Oxide. Issue 34 (26th July 2020) - Zhu, Zhiling; Bai, Qiang; Li, Shuo; Li, Siheng; Liu, Manhong; Du, Fanglin; Sui, Ning; Yu, William W.
Abstract: From manufacture to disposal, the interaction of graphdiyne based nanomaterials with living organisms is inevitable and crucial. However, the cytotoxic properties of this novel carbon nanomaterial are rarely investigated, and the mechanisms behind their cytotoxicity are totally unknown. In this study, the antibacterial activity of graphdiyne (GDY) and graphdiyne oxide (GDYO) is reported. GDY is capable of inhibiting broad‐spectrum bacterial growth while exerting moderate cytotoxicity on mammalian cells. In comparison, GDYO exhibits lower antibacterial activity than that of GDY. Then an alterable, synergetic antibacterial mechanism of GDY, involving wrapping bacterial membrane, membrane insertion and disruption, and reactive oxygen species generation is demonstrated, while the differential gene expression analysis indicates that GDY could only alter the bacterial metabolism slightly and the oxidative stress route may be a minor bactericidal factor. The investigation of the antibacterial behaviors of GDY based nanomaterials may provide useful guidelines for the future design and application of this novel molecular allotrope of carbon. Abstract : This work discloses the antibacterial mechanism of graphdiyne (GDY) and GDY oxide. The excellent bactericidal potency of GDY is primarily associated with physical destruction. The capability of GDY to wrap bacteria through physical adsorption and pierce bacterial membranes with sharp edges, results in leakage of intracellular substances and bacterial death. ROS‐induced oxidative stress serves a supporting role on bacterial inhibition.